BAWOR DAN KEARIFAN BUDAYA ISLAM JAWA BANYUMASAN - Werdi Agung Soewargono (IBDA` : Jurnal Kajian Islam dan Budaya, 2012)
This paper discusses Bawor as a local icon of the Banyumas. Baworis one of the characters that exist only in a clown-puppet in Banyumas.To understand Bawor, we need to understand the visual semiotics of personalitybased on his existing structure forms. Of these interpretations, itis understood that Bawor has characteristics of cablaka, glogok sor, innocent,critical, modest, and clamit, that is transformed the Banyumas society.Several personalities from Bawor in line with Islamic values becausepuppets that developing in Banyumas is the result of the spread of theteachings of Sunan Kalijaga.